Effectiveness of Addition Papain Enzyme in Artificial Diet on the Metamorphosis Rate and Glycogen Content of Mangrove Crab Larvae (Scylla olivacea) - Haryati, Haryati; Fujaya, Yushinta; Saade, Edison; Fajrianti, Dwi (Torani Journal of Fisheries and Marine Science, 2018)
In the rearing of fish larvae, artificial feed can be given when digestive enzymes have been produced. To improve the ability of fish larvae to utilize artificial feeds can be done with the addition of exogenous enzyme into the artificial feeds. The aim of this study was to determine the dose of papain enzyme and the correct predigest artificial feeding stadium on metamorphosis rate and glycogen content of mangrove larvae (Scylla olivacea). The experimental design used was a factorial pattern with a complete randomized baseline design, the first factor being the dose of papain enzyme (0%, 1.5%, 3.0% and 4.5%), while the second factor was the predigest artificial feeding stage (zoea 2 and 3).  The results showed that the difference of dose of papain enzyme and predigest artificial feeding stages had significant effect (p <0.05) on the metamorphosis rate of  7, 9, 10, 12, 13, 16 and 17 day larvae, but the interaction between them was not significant (p>0,05). The rate of metamorphosis at doses of enzyme papain was 0% and 1.5% longer and significantly different (p <0.05) compared to 3% and 4.5% doses. The rate of metamorphosis at doses of 3.0% and 4.5% was not significantly different (p> 0.05). The content of glycogen larvae in dose of enzyme papain 4,5% not different than dose 1,5% and 3,0% but higher and significantly different than dose 0%. Glycogen content at dose 0%, 1,5% and 3,0%. was not significantly different (p> 0.05). Based on the results of these studies to hydrolyze feed proteins can be used papain enzyme with a dose of 4.5%.Keywords: papain enzyme, metamorphosis rate, mangrove crab larvae (Scylla olivacea), glycogen content